Pathologic chemotherapy response score in epithelial ovarian cancer: Surgical, genetic, and survival considerations. (September 2020) - Barrington, David A.; Felix, Ashley S.; Owda, Rieham; Suarez, Adrian A.; Cohen, David W.; Senter, Leigha; Copeland, Larry J.; Fowler, Jeffrey M.; Backes, Floor J.; Cohn, David E.; Bixel, Kristin L.; O'Malley, David M.; et al.
Abstract: Objective: A pathologic chemotherapy response score (CRS) is used to grade ovarian cancer response to neoadjuvant chemotherapy (NACT). We evaluated the prognostic significance of the CRS in a single institution cohort. Methods: A retrospective review of all consecutive epithelial ovarian cancer patients undergoing interval debulking surgery (IDS) after NACT from 2016 to 2017 were included. Clinical, pathologic, surgical, outcomes, and genetic data were abstracted from medical records. CRS was assigned by pathology based on a section of omentum as follows: 1 = minimal response, 2 = moderate response, and 3 = near complete response. Results: Among the 50 subjects, 14 (28%) were classified as CRS1, 29 (58%) as CRS2, and 7 (14%) as CRS3. The majority of patients were diagnosed with high grade serous histology (94%). Most women in this cohort underwent either an optimal or complete cytoreduction to no gross residual disease (96%). Women in the CRS2 group were most likely to have a pathogenic variant (51.7%) while those in the CRS1 were least likely (7.1%). Most women recurred regardless of CRS. CRS was not associated with progression-free survival (log-rank p = 0.82) or overall survival (log-rank p = 0.30). Conclusions: Though previous data support the use of CRS as a prognostic indicator, we failed to show a correlation between CRS and survival in our continuous single institution cohort. The high rate of optimal debulking across all CRS groups in this study may mitigate the prognostic significance of the scoring system. Nevertheless, tumors that respond poorly to traditional chemotherapy should remain of avid interest for potential novel therapies. Highlights: Chemotherapy response score at time of surgery after NACT for ovarian cancer is not prognostic of survival. High rates of optimal debulking were achieved regardless of CRS. Development of novel therapies for tumors that respond poorly to chemotherapy remains of high importance.